Void growth and coalescence in a three-dimensional non-periodic void cluster. (15th May 2018) - Trejo Navas, Victor Manuel; Bernacki, Marc; Bouchard, Pierre-Olivier
Abstract: Void growth and coalescence are studied in this work through Finite Element simulations. A methodology for the study of three-dimensional non-periodic configurations is proposed. In order to avoid the hypothesis of microstructural periodicity, a three-dimensional cluster with three initially spherical voids, is modeled. Multiple spatial configurations are simulated in a parametric study. The pre-coalescence behavior is detailed through the evolution of the volume of each void, the minimum intervoid distance, and the equivalent plastic strain in the middle of the shortest path between voids, and the resulting coalescence mechanism is described. Locally accelerated and non-homogeneous void growth is observed close to the localization band. Although only coalescence by internal necking is present, apparent void-sheet formation is observed if only a two-dimensional slice is considered. These observations, and a comparison with the Rice–Tracey growth model, highlight the importance of fully considering the three-dimensional complexity of the ductile damage micromechanisms.